Phytochemical test of ketapang leaf (Terminalia catappa) with age variation and its application with EM4 on the growth of tilapia (Oreochromis niloticus) - Miska Sanda Lembang; Syarifatul Jannah; Christine Dyta Nugraeni; M. Gandri Haryono (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
Tilapia is a much-loved source of animal protein. The success of tilapia production is characterized by optimal fish growth. The process of growing tilapia has several problems including water quality. Fluctuating water quality causes fish to be easily stressed and susceptible to attack by pathogenic bacteria. Ketapang leaves have antibacterial properties because they contain metabolites. This research was conducted to determine the content of active compounds from variations in the age of ketapang leaves including young, old, and dry ages and their effect with EM4 on the growth and survival of tilapia (Oreochromis niloticus). This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Phytochemical tests on three types of ketapang leaves showed that dried ketapang leaves contained more metabolites, namely alkaloids, flavonoids, tannins and phenols. Based on the statistic analysis (ANOVA) showed that variations in each control treatment, young, old, and dry ketapang leaves had a significant effect on the absolute length growth and growth rate (SGR), but had no significant effect on the absolute weight and survival (SR) of tilapia (Oreochromis niloticus). However, from the three age variations of ketapang leaves, it was found that dry ketapang leaves were the best species for growing tilapia.